2021
DOI: 10.1111/hel.12788
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body size on first‐line Helicobacter pylori eradication success using vonoprazan and amoxicillin dual therapy

Abstract: Background As a first‐line therapy for Helicobacter pylori, dual therapy with vonoprazan and amoxicillin (VA‐dual) provides an eradication rate similar to that of vonoprazan‐based triple therapy. As the factors associated with the eradication rate of H. pylori with VA‐dual are unknown,we investigated them in this study. Materials and Methods Overall, 163 patients diagnosed with H. pylori infection received VA‐dual (vonoprazan 20 mg twice daily and amoxicillin 750 mg twice daily for 7 d). The association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Our results also reveal that higher eradication rates in patients with a low BSA level in both BDT and RADT groups. A previous study on vonoprazan‐based dual therapy 36 showed that H . pylori eradication success was associated with a low BSA level and smaller body size, which was consistent with the current results.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also reveal that higher eradication rates in patients with a low BSA level in both BDT and RADT groups. A previous study on vonoprazan‐based dual therapy 36 showed that H . pylori eradication success was associated with a low BSA level and smaller body size, which was consistent with the current results.…”
Section: Discussionmentioning
confidence: 99%
“…7,11,[14][15][16]18,19,22,26,27,[29][30][31][32][33][35][36][37][38][39][42][43][44][45][46][47][48] VPZ was included in the eradication regimen in 4 studies. 11,[16][17][18] In 7 studies, the duration of H. pylori treatment was 14 days. 10,14,19,21,22,24,35 In 12 studies, all the participants had peptic ulcer.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…10,14,19,21,22,24,35 In 12 studies, all the participants had peptic ulcer. 10,15,20,[23][24][25]28,32,34,37,39,46 Eleven studies 11,14,15,17,20,24,30,34,38,40,48 provided information about the current smoking status of the patients. In 5 studies 15,24,25,33,40 Reported odds ratios and 95% confidence intervals were used if available from the literature and calculated when unavailable.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in which the dual therapy consisted of 20 mg vonoprazan twice daily and 500 mg amoxicillin 3 times daily for 7 days as the first-line treatment provided a higher eradication rate of 93% [37]. Another study reported that smaller patient body size, including lower body mass index and lower body surface area, was associated with higher eradication success of the vonoprazan-amoxicillin dual therapy [38]. These study results suggest that vonoprazan-amoxicillin dual therapy with proper adjustment of amoxicillin dose based on patient body size is expected to be the ideal treatment in the future for minimizing both H. pylori antibiotic resistance development and posttreatment gut microbiota dysbiosis while also providing sufficient H. pylori eradication.…”
Section: Introductionmentioning
confidence: 99%